Structural rearrangement and change of cerium valence in cerium dioxide (CeO₂) nanocrystals - Boyko, Yu.I.; Seminko, V.V.; Maksimchuk, P.O.; Malyukin, Yu.V. (Functional Materials, 2016)
For CeO₂ nanocrystals a large number of cerium ions undergo Ce⁴⁺→ Ce³⁺ transition leading to formation of oxygen-deficient CeO₂₋x phase in the subsurface layer of nanocrystal. Such structural rearrangement leads to density gradient in ceria nanocrystals changing thereby the elastic constants of material. The analysis of free energy balance has shown that formation of highly deficient CeO₂₋x phase occurs inevitably for the nanocrystals with sizes d ≤ 6 nm.